FLOUR TREATMENT OF OYSTER MUSHROOM (Pleurotus Ostreatus) AND OLD DRIED NOODLES DRYING ON QUALITY OF WHEAT MOCAF (Modified Cassava Flour) - Budi Suarti; Misril Fuadi; Eko Budiono (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Noodle is one of the many popular food especially for the Indonesian people. Noodles made from wheat flour which is still imported by Indonesia. It is required to replace wheat flour. Alternative materials that can be used is mocaf. Mocaf has characteristics like wheat flour. The weakness of Mocaf is the absence of gluten and low protein content, therefore it needs to be added by source of protein like white oyster mushrooms.This research aimed to determine the effect of oyster mushroom flour and drying time on the quality of dried noodle from Mocaf. This research used a Rancangan Acak Lengkap (RAL) consisting of two factors, first is the addition of oyster mushrooms flour factor (5%, 10%, 15%, 20%) and second is drying time factor (20,40,60,80 minutes). Based on this research the best treatment of organoleptic properties was addition of oyster mushroom flour 5% and 20 minutes drying time, while in terms of chemistry at the addition of oyster mushrooms flour 20 % and 80 minutes drying time.Keywords : drying time, dried noodle, mocaf, oyster mushrooms flour.